Homesickness, Anxiety and Depression among Pakistani International Students in Indonesia during Covid-19 Outbreak - Shoukat, Shahzad; Callixte, Cyuzuzo; Nugraha, Jusak; Budy, Theresia Indah; Shoukat, Hamad (Jurnal Kesehatan Masyarakat, 2021)
International students are exposed to multiple mental health crisis due to social, environmental and culture shocks in foreign lands but it gets worse in presence of life- threatening disease outbreak. This research was conducted to evaluate the homesickness, anxiety and depression among Pakistani international students in Indonesia during Covid-19 Outbreak. Methods: This study was conducted on 86 random students that are pursuing their studies in different public and private universities in Indonesia. The data were collected by distributing google forms via email and social media groups and the responses from the respondents were recorded and analyzed statistically. The study findings revealed that there is a correlation between Covid-19 pandemic and the development of various mental health crisis where 33 students (38.37 %) developed homesickness, 11 students (12.79%) developed anxiety and 2 students (2.33 %) manifested low-grade depression. Homesickness was outstandingly observed in females (72.72 %) whereas anxiety was highly reported in males (90.90%).  The study findings demonstrated that there is a strong negative correlation between student financial statuses and the development of homesickness (r: -0.977, P: 0.023) and anxiety (r: -0.944, P:  0.056). All in all, the fear to contract coronavirus, lockdowns, financial instability, death toll of citizens and medical professionals, run out of medical facilities and social media hoaxes are significant risk factors of mental health crisis among Pakistani international students in Indonesia.